An Experimental Rat Model of Acute Pancreatitis and the Effect of Apigenin - Apostolos, Sovatzidis; Panagoula , Oikonomou; Eirini , Nikolaidou; Maria, Lambropoulou; Fotini, Papachristou; Apostolos , Papalois; Christos, Tsalikidis; Alexandra, Tsaroucha K. (New Horizons in Medicine and Medical Research Vol. 11, 2022)
The aim of the study was to investigate the effect of apigenin (AP) on acute pancreatitis (ACP) by measuring the values of interleukin-6 (IL-6), interleukin-18 (IL-18) and resistin (R) in serum and CD45 as well as high mobility group box 1 protein (HMGB1) in intestinal tissue using a rat experimental model. 126 male Wistar rats were used, divided in three groups: Sham (S), Control (C) and Apigenin (Ap). The S group underwent laparotomy and closure of the abdominal wall. The C group underwent ligation of the pancreatic duct to induce acute pancreatitis. The apigenin group after induction of ACP, received AP. Blood and intestinal tissue were collected. Following AP administration, IL-6 and IL-18 in serum decreased as well as HMGB1 and CD45 in intestinal tissue. In contrast R remained at low levels in the Ap group. In a bilio-pancreatic duct ligation experimental model of ACP, AP treatment appears to protect intestinal and serum parameters, lowering the severity of ACP. As a result, giving this substance to humans could reduce the damage to the organs affected in the early stages of ACP.